Fish Talk - Adlam, Robert G. (Anthropologica, 2022)
The article draws on recorded interviews under taken over the course of three summers of fieldwork among Aboriginal fishers of the Miramichi river of northern New Brunswick. Here particular attention is given to the discourse of these fishers, taken to mean their "talk" about the fishery. Indeed it is through such talk that the fishery is at once created and transformed reflecting in part past practice based on family gill net operations, and in more recent years, the experience of a highly regulated and waged trap net operation. It is hoped that the article will contribute to our understanding of the discursive construction of economy especially as this relates to the practices of Aboriginal riverine fishers.